THE INFLUENCE OF ADVERTISING ON REPURCHASE INTENTION OF LUWAK WHITE KOFFIE PRODUCTS AMONG CONSUMERS AMONG LP3I MEDAN POLYTECHNIC STUDENTS - Maulidina Maulidina (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Repurchase interest is purchase interest that is based on previous purchasing experiences. Advertising is a form of personal or paid communication about an organization, goods, services, or ideas by a known social media or company. This research aims to determine "The Influence of Advertising on Repurchase Intention for Luwak White Koffie Products among Consumers Among LP3I Medan Polytechnic Students". The preparation of this research uses quantitative methods, where this research is to ask about the relationship between two or more variables by collecting data using statistical (numerical) data analysis to test a series of hypotheses that have previously been determined with the help of the SPSS 25.00 application. The population in the study were students in all study programs with the 2020 standard at the LP3I Medan Polytechnic and the research sample was 49 people. Based on the results of the partial test research (t test) it shows that the t value is 7.889 < t table value 1.677 with a sig probability of 0.000 > 0.05, so it can be said that Advertising has a significant eflect on Repurchase Intention for Luwak White Koffie Products among Consumers Among LP3I Polytechnic Students Field, thus H1 is accepted and H0 is rejected. And the value of R Square obtained is 0.570 (57%). This shows that the dependent variable (Repurchase Intention) has a strong ability (0.60-0.799) in explaining variations in the dependent variable in this study.